2019
DOI: 10.1186/s10020-019-0085-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-122 promotes hepatic lipogenesis via inhibiting the LKB1/AMPK pathway by targeting Sirt1 in non-alcoholic fatty liver disease

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is a common hepatic disease with an increasing prevalence but an unclear aetiology. This study aimed to investigate the functional implications of microRNA-122 (miR-122) in the pathogenesis of NAFLD and the possible molecular mechanisms. Methods Both in vitro and in vivo models of NAFLD were generated by treating HepG2 and Huh-7 cells with free fatty acids (FFA) and by feeding mice a high-fat diet (HFD), respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(109 citation statements)
references
References 47 publications
(53 reference statements)
0
108
0
1
Order By: Relevance
“…miR-122 seems also responsive to diet in both in vitro and in vivo models and in humans. In particular, miR-122 appears upregulated in the presence of a high-fat diet, thus resulting in the promotion of lipogenesis in the liver [ 162 ].…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…miR-122 seems also responsive to diet in both in vitro and in vivo models and in humans. In particular, miR-122 appears upregulated in the presence of a high-fat diet, thus resulting in the promotion of lipogenesis in the liver [ 162 ].…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…In contrast, Long et al found that FFAs or HFD upregulated miR-122 in hepatocytes-derived HepG2 and HuH7 cell lines and in mice, respectively, revealing that miR-122 may promote lipogenesis by suppressing Sirt1. Indeed, miR-122 knockdown mitigated hepatic steatosis via Sirt1-induced liver kinase B1/AMP-activated protein kinase (LKB1/AMPK) pathway [131].…”
Section: Mirnas-diet Crosstalk In Nafld: How Unhealthy Dietary Habitsmentioning
confidence: 99%
“…In our study, a similar association between the expression level of DGCR9 and HCC patient OS was also observed, though our study included patients with HBV either positive or negative. Furthermore, in the network analysis (Figure 5a and Figure 5b), we showed that DGCR9 (ENSG00000273032) might act as a ceRNA to intervene in HCC pathogenesis by competitively associated to miR-122 and miR-885, which have been found to be involved in liver diseases or liver cancer [45][46][47]. All these results call for further studies to conclude a causal association between these relationships, which may contribute to novel targeted therapy.…”
Section: Discussionmentioning
confidence: 73%